Assessment of the Excavation Damaged Zones in the Surrounding Rock of an Underground Powerhouse under High In Situ Stress Using an Acoustic Velocity Detecting Method. (4th July 2020) - Zhang, Liguo; Wang, Dong; Dong, Jiaxing
Abstract : Excavation damaged zones (EDZs) in deeply buried underground powerhouse have become major obstacles to design and support, which potentially threaten safety and stability and increase construction and support costs. In this study, investigations of the EDZs were performed by applying an acoustic velocity detecting method in Houziyan hydropower project, southwest of China. A total of 38 testing boreholes distributed in high sidewalls of the main powerhouse were carried out, and corresponding 153 curves were obtained and analyzed. Then, EDZs were divided into highly damaged zone (HDZ), slightly damaged zone (SDZ), and excavation influence zone (EIZ), respectively. Furthermore, we classified the wave velocity curves into four categories: type I, type II, type III, and type IV. EDZs were qualitatively assessed based on the curve categories; in addition, we used a qualitative assessment method, which mainly involved an index of damage degree named D. The assessment results show that HDZ, but not SDZ, was significantly asymmetrically distributed in the upstream (average depth of 4.1 m) and downstream (average depth of 7.5 m) high sidewalls; in partial areas, depth of HDZ exceeded the length of designed rock bolts, which indicates that rock bolts cannot restrain crack development and EDZs evolution. Generally, EDZs distribution was consistent with deformation and failure phenomena distribution; compared to the field failure phenomena, the assessment results were reliable and reasonable. Finally, EDZs formation mechanism was discussed, and it can be concluded that the relatively large intermediate principal stresses σ 2 were a critical driving factor of the EDZs evolution.